Elephants Never Forget - Lorraine Lee
The Little Readers Series is designed to teach young children, especially Asian children how to read English. It is of equal importance to parents and teachers wishing to encourage children to understand the environmental and cultural:differences that are a part. of Asian life. Mrs. Lorraine Lee, the author and designer of the programme, has a background in Early Childhood Education and Child Psychology with many years of experience teaching Asian children how to read. With a need for an interesting and relevant reading programme, the Little Readers Series was produced to make reading easy and enjoyable. Parents and teachers will find the series a wonderful collection of humorous and entertaining stories, graded and easy to use. Reading should be fun and with the Little Readers Series, every reading time is fun time.